Heart-beguiling Araby the english romance with Arabia - Tidrick, Kathryn (Tauris Parke Paperbacks, 2010)
For certain Englishmen the Arabian desert and its inhabitants have always exercised a powerful fascination. By the early nineteenth century, a tradition of writing about the Arabs was flourishing. This book tells the story of a deep and lasting obsession and its effect on the very different men who experienced it